Politeness: How The Youth Of Banjarese Address People In Banjar Language - Adetya Nor Rizkyka (Pahlawan, 2022)
Politeness as part of language aspect is an important matter to discuss in language. Politeness deals with the term of addressing particular people which is important in Banjarese language as it shows respect and sentences tone. This article discusses the words used by Banjarese youth in addressing people. The writer observed the interaction between youth and elderly during the Ied Fitri holiday and presented the result on the tables. The result is expected to give a theoretical contribution on the language discussion. Abstrak: Kesantunan sebagai bagian dari aspek berbahasa merupakan hal yang penting untuk dibahas dalam berbahasa. Sopan santun berkaitan dengan istilah menyapa orang tertentu yang penting dalam bahasa Banjar karena menunjukkan rasa hormat dan nada kalimat. Artikel ini membahas tentang kata-kata yang digunakan oleh pemuda Banjar dalam menyapa orang. Penulis mengamatiinteraksi antara pemuda dan orang tua selama liburan Idul Fitri dan mempresentasikan hasilnya di atas meja. Hasil penelitian ini diharapkan dapat memberikan kontribusi teoritis pada pembahasan bahasa.